Pengaruh Mentoring dan Coaching terhadap Pengembangan Karir Guru dengan Kepercayaan Diri sebagai Variabel Intervening di SMA N 2 Pulau Punjung - Shelfi Amanda Putri; Ramdani Bayu Putra; Mardhatila Fitri Sopali (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the influence of mentoring and coaching on teacher career development with self-confidence as an intervening variable at SMA Negeri 2 Pulau Punjung. The research is motivated by the phenomenon of fluctuations in teacher career development over the last three years. The research method used is quantitative, with a population and sample of 50 teachers using a total sampling technique. Data collection was carried out through Likert scale questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results found that mentoring has a positive and significant effect on career development, but coaching and self-confidence do not significantly affect career development. Additionally, coaching has a significant effect on self-confidence, while mentoring does not. Self-confidence was also found unable to mediate the influence of mentoring or coaching on teacher career development at SMA Negeri 2 Pulau Punjung. These results are expected to contribute to school management in improving human resource quality through more effective and targeted development programs in the future.